Recensioner, Vol. 51 No. 1-2 (2021) - Brudin Borg, Camilla; Forsgren, Peter; Fjelkestam, Kristina; van Ooijen, Erik; Ohlsson, Anders; Ekedahl, Nils; Skafte Jensen, Minna; Annell, Cecilia; Theander, Birgitta; Olsson, Jesper; m.fl. (Tidskrift för litteraturvetenskap, 2021)
Reviews of recent publications in the field.